The use of paracetamol during pregnancy: A qualitative study and possible strategies for a clinical trial. - Cathrine Vedel; Ditte Staub Jørgensen; David Møbjerg Kristensen; Olav Bjørn Petersen; Gorm Greisen (PLoS ONE)
Paracetamol (N-acetyl-p-aminophenol (APAP), also known as acetaminophen) is used to relieve mild to moderate pain and reduce fever. APAP is widely used during pregnancy as it is considered safe when used as directed by regulatory authorities. However, a significant amount of epidemiological and experimental research suggests that prenatal exposure potentially alters fetal development. In this paper, we summarize the potentially harmful adverse effects of APAP and the limitations of the current evidence. It highlights the urgent need for a clinical trial, and the aim of the presented qualitative pilot study on APAP use during pregnancy is the feasibility of a large-scale randomized controlled trial (RCT). In the qualitative study, we included 232 Danish women from three hospitals in the spring of 2021. After recognizing the pregnancy, 48% had taken any APAP, and 6% had taken it weekly or more than weekly. A total of 27% who had taken APAP in the first trimester of pregnancy (even rarely) would potentially participate in an RCT. In a potential clinical trial, the women would need to be included early in the 1st trimester as the suspected harmful effects of APAP lies within this early reproductive developmental window. A possible recruitment strategy was explored. These data suggest that the target population appears positive towards an RCT. As a negative attitude among users has been considered the major hindrance for such a study, we cannot see hindrances for performing an RCT.